Interventions In Perfectionism: The effectiveness of cognitive-behavioral therapy (Research, Society and Development, 2024)
Cognitive-behavioral therapy (CBT) postulates that the interpretation of a given situation directly influences physical, behavioral, and emotional reactions, with symptom improvement occurring when dysfunctional thinking is modified, leading to changes in dysfunctional beliefs. Perfectionism can significantly affect mental and physical health levels, playing a critical role in psychopathologies and highlighting behavioral and cognitive aspects. Objective: To reflect on student training provided through clinical internship experience at a Higher Education Institution (HEI) in Teresina – Piauí, contributing to the practice and development of future professionals. Methodology: This is a qualitative research study of theoretical depth, based on an experiential model, where the type of textual production is an academic experience, with the primary characteristic being the description of the intervention. Results: Cognitive-behavioral therapies have been suggested for different audiences, demands, and contexts. Considering the findings during the sessions, it is evident that the techniques showed good adherence and effectiveness in treating perfectionism.